(untitled) (Journal of Contemporary Educational Policies and Practices, 2019)
Teaching English for ethnic minority students in remote Northwest area of Vietnam has always been a huge challenge for educators and teachers. With specific difficulties of the Northwestern region such as: the lack of basic learning facilities in rural schools; the majority of the students are ethnic minority people; students need to travel very long distances to school in small and dangerous paths in severe weather conditions and natural disasters all year round. Consequently, students lose learning motivation. This research presents some basic knowledge about motivation and indicates some key factors to motivate ethnic minority students in rural schools in the Northwest of Vietnam to study English effectively.